TMJ DISC DISLOCATION - CHALLENGE AND APPROACH - Alina Mihaela Apostu; Arina-Alice; Laura Checheriță; Oana Țănculescu (Romanian Society of Oral Rehabilitation, 2020)
The treatment of disc dislocations can be a frustrating experience for both the patient and especially for the doctor. Frequently it is difficult to determine what strategy is necessary, the decision oscillating between conservative and surgical interventions. The present study focuses on disc dislocation symptoms and the treatment used. There are specific age groups affected, predominantly females, and those with professions that involve vicious positions. Approximately 50% of patients have general pathologies that can cause disc dislocation. A large proportion of patients have occlusion disorders due to previous orthodontic and prosthetic treatments. Pain, reduced amplitude and asymmetry of mouth opening are symptoms in all cases. The treatment must be etiological not just symptomatic.